2011
DOI: 10.1111/j.1755-148x.2011.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

MEK–ERK and heparin‐susceptible signaling pathways are involved in cell‐cycle entry of the wound edge retinal pigment epithelium cells in the adult newt

Abstract: Summary The onset mechanism of proliferation in mitotically quiescent retinal pigment epithelium (RPE) cells is still obscure in humans and newts, although it can be a clinical target for manipulating both retinal diseases and regeneration. To address this issue, we investigated factors or signaling pathways involved in the first cell‐cycle entry of RPE cells upon retinal injury using a newt retina‐less eye‐cup culture system in which the cells around the wound edge of the RPE exclusively enter the cell cycle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 80 publications
3
37
0
Order By: Relevance
“…On the other hand, over-activation of Wnt/β-catenin signaling impairs RPE patterning during mouse eye development [17], [18], [19]. In support of Wnt maintaining the RPE quiescent, we have shown that when newt retina-less eye cups are injured and cultured with Wnt signaling inhibitor Dickkopf1 (Dkk1), there is an increase in cell proliferation at the edges of the injured RPE [60]. Taken together, our results suggest that both the retinal stem/progenitor cells of CM and cells of the RPE respond to injury by changing their nuclear β-catenin patterns and their proliferative status.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, over-activation of Wnt/β-catenin signaling impairs RPE patterning during mouse eye development [17], [18], [19]. In support of Wnt maintaining the RPE quiescent, we have shown that when newt retina-less eye cups are injured and cultured with Wnt signaling inhibitor Dickkopf1 (Dkk1), there is an increase in cell proliferation at the edges of the injured RPE [60]. Taken together, our results suggest that both the retinal stem/progenitor cells of CM and cells of the RPE respond to injury by changing their nuclear β-catenin patterns and their proliferative status.…”
Section: Discussionmentioning
confidence: 98%
“…The newt RPE has also been studied with respect to the molecular mechanism of cell entry into the S-phase after RPE separation from the NR [62,63]. The authors of the first study analyzed an activity of MEK-ERK signaling in RPE just after NR removal from the newt eye and found it activated within 30 min after retinectomy.…”
Section: Proliferative Activity Of Adult Newt Rpe Cells In the Coumentioning
confidence: 99%
“…In the second study, changes in the MEK–ERK cascade were analyzed in short-term in vitro cultures of the posterior eye segments without the NR, and activation of MEK–ERK was observed within 1 h after dissection. In both cases, the authors attribute these results to upregulation of each component of the MEK–ERK pathway by a positive feedback mechanism [62,63]. It is noteworthy that the timing of RPE cell entry into the phase of DNA synthesis differs depending on the newt species and the kind of surgery, but, in any case, this occurs within the first 10 days after RPE separation from the NR [10].…”
Section: Proliferative Activity Of Adult Newt Rpe Cells In the Coumentioning
confidence: 99%
“…Thus far, to address how retinal regeneration in the adult newt is triggered, we have investigated cellular events and signaling pathways that are involved in cell cycle re-entry of RPE cells [8,9,10] as well as their acquisition of multipotent properties [3,11]. Our studies have predicted that at least two elements are necessary for cell cycle re-entry of RPE cells: mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) kinase (MEK)-ERK intracellular signaling activity and release from inhibition mediated by cell–cell contact [9]. However, it is still to be studied how MEK-ERK signaling activity is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we addressed these issues using our original in vitro system in which we can carry out retinectomy in a dish and follow the behaviour of RPE cells under controlled conditions [9]. We finally found that MEK-ERK signaling activity, which was enhanced by retinectomy (the first step of the trigger), was a prerequisite for β-catenin signaling that was stimulated by attenuation of the cell–cell contact (the second step of the trigger).…”
Section: Introductionmentioning
confidence: 99%